2017
DOI: 10.4103/ijo.ijo_684_15
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure and its correlation with midnight plasma cortisol level in Cushing's disease and other endogenous Cushing's syndrome

Abstract: Purpose:The purpose of this study is to measure intraocular pressure (IOP) and evaluate the correlation between IOP and midnight plasma cortisol (MPC) level in patients with Cushing's disease (CD) and other endogenous Cushing's syndrome (ECS).Methods:This is a cross-sectional study from a single center including newly diagnosed patients with CD or ECS. All patients underwent detailed ophthalmological evaluation. IOP was measured by Goldmann applanation tonometry in the morning and evening on two consecutive da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…The case had normalized IOP at one-year follow-up in a glaucoma clinic. Mishra et al reported that seven out of 22 patients had increased IOP in the CD cohort 11 . Though they found mean serum cortisol level was lower in patients with normal IOP comparing to those with high IOP, the difference was not statistically signi cant.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The case had normalized IOP at one-year follow-up in a glaucoma clinic. Mishra et al reported that seven out of 22 patients had increased IOP in the CD cohort 11 . Though they found mean serum cortisol level was lower in patients with normal IOP comparing to those with high IOP, the difference was not statistically signi cant.…”
Section: Discussionmentioning
confidence: 97%
“…It was well known that systemic steroid was a signi cant risk factor for increased intraocular pressure (IOP) 5,6 , and the incidence may rise to 30-40% of the general population due to topical or systemic glucocorticoids usage 7,8 . However, only several case reports and two cohort studies [9][10][11] investigated the association between increased IOP and endogenous hypercortisolemia. The association between glaucoma and excessive endogenous cortisol, as well as the ophthalmological outcomes after endocrine remission due to a surgical resection were still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The case had a normalized IOP at the 1-year follow-up in a glaucoma clinic. Mishra et al11 reported that 7 of 22 patients had increased IOP in a CD cohort. Although they found that the mean serum cortisol level was lower in patients with normal IOP compared with those with a high IOP, the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Several case reports have also investigated ocular hypertension in CD due to its high endogenous cortisol level. [9][10][11][12] However, the incidence of ocular hypertension in endogenous hypercortisolemia, as well as the IOP change after endocrine remission due to a surgical resection, remain unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation